Evaluation of the Efficacy of BCG in Protecting Against Contact Challenge With Bovine Tuberculosis in Holstein-Friesian and Zebu Crossbred Calves in Ethiopia - Bayissa, Berecha; Sirak, Asegedech; Worku, Adane; Zewude, Aboma; Zeleke, Yemisrach; Chanyalew, Mahlet; Gumi, Balako; Berg, Stefan; Conlan, Andrew; Hewinson, R. Glyn; , The ETHICOBOTS Consortium; Wood, James L. N.; et al. (Frontiers in Veterinary Science, 2021)
Bovine tuberculosis (bTB) is prevalent in intensive dairy farms in Ethiopia. Vaccination could be an alternative control approach given the socio-economic challenges of a test-and-slaughter control strategy. The efficacy of the BCG was evaluated on 40 Holstein-Friesian (HF) and zebu crossbred calves recruited from single intradermal cervical comparative tuberculin (SICCT) test negative herds and randomly allocated into two groups. Twenty-two calves were vaccinated within two weeks of age, and 18 were kept as a control. Six weeks post-vaccination, the two groups were exposed and kept mixed with known SICCT test positive cows for one year. Immune responses were monitored by interferon gamma (IFN-) release assay (IGRA), SICCT test and antibody assay. Vaccinated calves developed strong responses to the SICCT test at the sixth week post-vaccination, but didn’t respond to ESAT-6/CFP-10 peptide antigens-based IGRA. During the exposure, IFN- response to the specific peptides cocktail (F(2.44, 92.67) = 26.96; p < 0.001) and skin reaction to the specific proteins cocktail (F(1.7, 64.3); p < 0.001) increased progressively in both groups while their antibody responses were low. The prevalence of bTB was 88.9% (95% CI: 65.3–98.6) and 63.6% (95% CI: 40.7–83.8) in the control and vaccinated calves, respectively, based on M. bovis isolation, giving a direct protective efficacy estimate of 28.4% (95% CI: -2.7–50.1). The proportion of lesion in vaccinated calves was 7.0% (34/484) against 11.4% (45/396) in control calves, resulting in a 38% (95% CI: 5.8–59.4) reduction of lesions. Besides, the severity of pathology was significantly lower (Mann Whitney U test, p < 0.05) in vaccinated (Median score = 2.0, IQR = 0 – 4.75) than in control (Median score = 5, IQR = 3.0 – 6.25) calves. Moreover, survival from M. bovis infection in vaccinated calves was significantly (Log-rank test: χ2= 7.796, p < 0.01) higher than that of the control calves. In conclusion, the efficacy of BCG was low, but the reduced frequency and severity of lesion in vaccinated calves could suggest its potential role in containing onward transmission.